STRATEGI PELAKSANAAN SURAT KEPUTUSAN REKTOR NOMOR 2862 TENTANG UANG KULIAH TUNGGAL DI UNIVERSITAS RIAU - MUSTHAFA HUSEIN LUBIS; SUJIANTO " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The Implementation Strategy of the Decree No. 2862 On Rector Single Tuition at the University of Riau. In order to provide opportunity and equality for all communities to enjoy Higher Education , the Directorate General of Higher Education issued a decree number 97/E/KU / 2013 on the Application Tuition Single ( UKT ) to all State Universities . Refrency the decision to the Minister of Education and Culture, number 53 of 2013 on Single Tuition and Tuition Single . University of Riau as one college and then apply for State Tuition single system with the birth of Riau University Rector Decree number 2862. The results of this study indicate that not maximal execution About Single Tuition at the University of Riau . This is evident from not delivered optimally goals and objectives so that the rejection of Students University of Riau , work flow implementation that does not fit , no supervision is done so that the policy can be implemented Single Tuition in accordance with the objectives , and the absence of clear and unequivocal sanctions against violations - abusesKeywords : Strategy Implementation , Single Tuition , University of Riau